2011
DOI: 10.1111/j.1708-8208.2011.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Overdentures in the Edentulous Mandible Supported by Implants and Retained by a Dolder Bar: A 5‐Year Prospective Study

Abstract: Dolder bars to restore oral implants in the edentulous mandible appear to offer a high rate of implant survival, good stability of the peri-implant tissue, and a low rate of prosthetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…In the majority of studies, a 2-stage surgical procedure and a conventional loading protocol were carried out, but non-submerged healing (1-stage surgery) followed by immediate prosthetic loading was applied, as well (Table 3) Richter & Knapp (2010) performed either bone splitting or bone spreading but no augmentation in case of heavy bone resorption. Three other studies Heschl et al 2013;Lorenzoni et al 2013) reported not to have applied augmentative or regenerative procedures. The rest of the studies cannot be commented as the authors did not make any statements about bone augmentation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the majority of studies, a 2-stage surgical procedure and a conventional loading protocol were carried out, but non-submerged healing (1-stage surgery) followed by immediate prosthetic loading was applied, as well (Table 3) Richter & Knapp (2010) performed either bone splitting or bone spreading but no augmentation in case of heavy bone resorption. Three other studies Heschl et al 2013;Lorenzoni et al 2013) reported not to have applied augmentative or regenerative procedures. The rest of the studies cannot be commented as the authors did not make any statements about bone augmentation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Different retaining systems for overdentures have been reported in the literature with satisfactory clinical results (5). Some of the commercially available retaining systems for overdentures are: O'ring attachment, bar-clip system, locators and telescopic crowns (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…As a prospective long‐term investigation concerning older individuals, it is not surprising to see a significant annual dropout rate, consistent with previous medical studies which noted older individuals as more likely to dropout due to co‐morbid conditions (Launer, Wind, & Deeg, ; Rockwood, Stolee, Robertson, & Shillington, ). Nevertheless, having obtained a full set of data at 5 years from 67 out of 80 participants (83.75%) allows for a relatively large sample size within the field and can support reliable conclusions (Elsyad, ; Heschl et al, ). At the terminal point of data collection, the cumulative implant survival rate reached 98.72% which is higher than many reported in other long‐term prospective clinical studies (Balaguer, Ata‐Ali, Peñarrocha‐Oltra, García, & Peñarrocha‐Diago, ; Meijer, Raghoebar, & Van‘t Hof, ).…”
Section: Discussionmentioning
confidence: 99%